Driving and sustaining culture change in Olympic sport performance teams: A first exploration and grounded theory - Cruickshank, A.; Collins, D.; Minten, S. (Journal of Sport & Exercise Psychology, 2014)
Stimulated by growing interest in the organizational and performance leadership components of Olympic success, sport psychology researchers have identified performance director-led culture change as a process of particular theoretical and applied significance. To build on initial work in this area and develop practically meaningful understanding, a pragmatic research philosophy and grounded theory methodology were engaged to uncover culture change best practice from the perspective of newly appointed performance directors. Delivered in complex and contested settings, results revealed that the optimal change process consisted of an initial evaluation, planning, and impact phase adjoined to the immediate and enduring management of a multidirectional perception- and power-based social system. As the first inquiry of its kind, these findings provide a foundation for the continued theoretical development of culture change in Olympic sport performance teams and a first model on which applied practice can be based.